1990
DOI: 10.1007/bf02390649
|View full text |Cite
|
Sign up to set email alerts
|

The role of bacterial vaginosis as a cause of amniotic fluid infection, chorioamnionitis and prematurity — a review

Abstract: Antepartum bacterial vaginosis in pregnancy has been related to premature delivery, the recovery of microorganisms from amniotic fluid of women in premature labor with intact membranes, to histologic chorioamnionitis and to the recovery of microorganisms from the placenta or membranes. Microorganisms associated with bacterial vaginosis are commonly recovered from the amniotic fluid and chorioamnion of patients who deliver prematurely. In addition, bacterial vaginosis is associated with maternal infectious morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
1
10

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(100 citation statements)
references
References 27 publications
0
89
1
10
Order By: Relevance
“…Although the etiology of preterm labor and delivery is unknown, there is overwhelming epidemiological, pathological, and immunological evidence to implicate the infection of the uteroplacental unit as a causative factor in a substantial number of preterm births (10 -12). Infection-related prematurity is most likely caused by an infection that ascends from the lower genital tract to the upper tract, with the end stage being a positive amniotic fluid culture (13,14). Fetal exposure to high concentrations of microorganisms leads to colonization of the fetus lung airways and subsequent pneumonia, sepsis, and meningitis (15,16).…”
mentioning
confidence: 99%
“…Although the etiology of preterm labor and delivery is unknown, there is overwhelming epidemiological, pathological, and immunological evidence to implicate the infection of the uteroplacental unit as a causative factor in a substantial number of preterm births (10 -12). Infection-related prematurity is most likely caused by an infection that ascends from the lower genital tract to the upper tract, with the end stage being a positive amniotic fluid culture (13,14). Fetal exposure to high concentrations of microorganisms leads to colonization of the fetus lung airways and subsequent pneumonia, sepsis, and meningitis (15,16).…”
mentioning
confidence: 99%
“…& Eschenbach, D.A found that the role of bacterial vaginosis as a cause of amniotic fluid infection, chorioamnionitis and prematurity [10] .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years a renewed interest has emerged about vaginal infections with Gardnerella vaginalis, particularly in relation to its association with perinatal diseases [4,8,16,201. This bacteria is found in 24 to 37% of patients attending sexually transmitted diseases clinics and is most prevalent in individuals between 20 and 24 years of age .…”
Section: Ultrastructural Characteristics Of Gardnerella Vaginalis Infmentioning
confidence: 99%